Variations in the Life Histories of Incarcerated Parents by Race and Ethnicity: Implications for Service Provision. (2nd January 2017) - Miller, Keva M.; Eddy, J. Mark; Borja, Sharon; Lazzari, Sarah R.
ABSTRACT: Incarcerated parents have complex life histories that often remain unresolved during incarceration, can continue to create barriers to prosocial success on release, and present similar intergenerational challenges for their children. This study examines the life histories of incarcerated fathers and mothers from the Pacific Northwest and how their experiences vary based on race and ethnicity. Five areas examined were exposure to trauma, child welfare involvement, mental health and substance abuse problems, juvenile justice and adult criminal justice involvement, and intergenerational criminal justice involvement. The sample comprised 359 incarcerated parents, and their racial/ethnic composition was 59% White, 14% African American, 11% multiracial, 8% Native American, and 7% Latino. Few differences were found across racial and ethnic groups. Mothers appeared more similar to each other across groups than fathers. Results illustrated similarities yet some surprising differences with national trends on key study variables. Implications for future research and intervention and prevention are discussed.